The effect of organic acids on the behaviour and biodegradation of 14C-phenanthrene in contaminated soil. (April 2020) - Vázquez-Cuevas, Gabriela M.; Lag-Brotons, Alfonso J.; Ortega-Calvo, Jose J.; Stevens, Carly J.; Semple, Kirk T.
Abstract: The interaction between root exudates and soil microbes has been hypothesised as the primary mechanism for the biodegradation of organic pollutants in the rhizosphere. However, the mechanisms governing this loss process are not completely understood. This study aimed to investigate the effect of two important compounds within root exudates (citric and malic acid) on 14 C-phenanthrene desorption and bioaccessibility in soil. Overall results showed that the presence of both citric and malic acid (>100 mmol l −1 ) enhanced the desorption of 14 C-phenanthrene; this appeared to be concentration dependant. Increases in extractability were not reflected in a higher bioaccessibility. Despite enhancing the desorption of 14 C-phenanthrene in soil, there is no direct evidence indicating that citric or malic acid have the ability to promote the biodegradation of 14 C-phenanthrene from soil. Results from this study provide a novel understanding of the role that substrates, typically found within the rhizosphere due to root exudation, play in the bioaccessibility and biodegradation of hydrocarbons in contaminated soil. Highlights: Organic acids found within the rhizosphere play an important role on the behaviour of PAHs in soil. The total extractable fraction of 14 C-phenanthrene from soil can be increased by citric and malic acid. Increases on the PAH extractability in the presence of the organic acids were not reflected in increases in biodegradation.